Pengaruh Brand Image dan Kepercayaan terhadap Loyalitas Deposan di BRI Syariah Kantor Cabang Suniaraja Bandung - Jujun Jamaludin; Asep Abdul Halim; Linda Pratiwi (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to determine how the influence of Brand Image, trust on the loyalty of depositors at BRI Syariah KC Suniaraja Bandung, while the type of research is quantitative associative, the type of data is primary data and uses data collection in the form of observations, interviews, questionnaires and literature studies. The results showed that there was a significant influence between Brand Image on the loyalty of depositors at BRI Syariah KC Suniaraja Bandung with the results of the t test where the value of t count > t table (4.424 > 1.666) there was a significant influence between trust and loyalty of depositors at BRI Syariah KC Suniaraja Bandung with t test results where t count > t table (4.365 > 1.666), and simultaneously there is a significant influence between brand image and trust on depositor loyalty at BRI Syariah KC Suniaraja Bandung with f test results where f count > f table ( 17,177 > 3,128).